Evolution of Employment Laws that Guarantee Women in Bolivia - Rodríguez, Nicolás (2023)
This work presents the evolution of regulations to provide equal employment opportunities for men and women in Bolivia. It emphasizes national regulation (laws, supreme decrees, international agreements, and other formal State regulations) that encourage women’s integration into the STEM (Science, Technology, Engineering, and Mathematics) job market.